Profil Pengetahuan, Kompetensi, Dan Sikap Sains Siswa Melalui Pendekatan Contextual Teaching And Learning (CTL) Dalam Pembelajaran Ipa Terpadu - Tanty Purwanty; Usep Soetisna; Uus Toharudin (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
This study aims to describe the profile of knowledge, competence, and attitude of students' science and students' and teachers' responses as a result of Integrated Science lesson with Contextual Teaching and Learning (CTL) approach to the concept  of Global Warming. This research method using quasi eksperimental research. The sample in this study is the seventh grade students of SMP Sultan Agung Source academic year 2016/2017. With cluster random sampling technique, VII B class samples were selected as experimental class which was studied by CTL approach and class VII A as control class subjected to conventional learning. The instrument used is a multiple choice question test that amounts to 25 with attention to indicators leading to the science literature Frame work PISA 2015; A questionnaire of students' science stance and student responses; Teacher interview as teacher response; and observation of learning. Data analysis was performed using Excel 2010 and SPSS 22.0 for Windows. Based on the data analysis of the research results concluded that: (1) Improved students' science knowledge profile as a result of IPA learning Integrated with CTL approach on global warming concept with N-gain 0.59 medium category (2) Increase of students' science competency profile as a result of IPA learning Integrated with CTL approach on global warming concept with N-gain 0.59 medium category (3) Improved students' science attitude profile as a result of IPA learning Integrated with CTL approach on global warming concept with N-gain 0.04 low category (4) Student responses to IPA learning Integrated with CTL approach on the concept of global warming responded positively 81%. The results of this study are expected to be input in the framework of improving the quality of integrated science learning in junior highKeywords: Knowledge; Competence; Attitude;Science Literacy; Contextual  Teaching and Learning Approach (CTL)